A Gastronomic Journey: Analyzing Kebon Ayu Village's Culinary Tourism Potential and Community Readiness - Dayu Made Sugiartini (Advances in Tourism Studies, 2023)
This study assesses the readiness of the Kebon Ayu Village community, particularly its traders, in effectively managing the Culinary Tourism Destination in Kebon Ayu Village, Gerung District, West Lombok Regency. Our investigation focuses on two primary aspects: the untapped potential of culinary tourism in this locale and the community's level of preparedness to harness this potential. Utilizing a combination of observational techniques, interviews, and document analysis, we scrutinized the current state of culinary tourism in Kebon Ayu Village. Our findings reveal several key areas that demand immediate attention: the cleanliness of tourist attractions, which poses a significant challenge due to littering and improper waste disposal practices by some visitors; accessibility, as the absence of clear road signage guiding tourists to culinary attractions hampers ease of access; and culinary diversity and menu information, as culinary offerings lack the diversity expected by tourists, and there is a lack of informative menu lists to aid their choices. In conclusion, our study underscores the immense potential of culinary tourism in Kebon Ayu Village but highlights the urgent need to address these issues to unlock this potential fully. Our research serves as a valuable resource for community leaders, policymakers, and stakeholders seeking to enhance the local culinary tourism experience